RASTA-Bacteria: a web-based tool for identifying toxin-antitoxin loci in prokaryotes - Sevin, Emeric W (BioMed Central, 2007)
Toxin/antitoxin (TA) systems, viewed as essential regulators of growth arrest and programmed cell death, are widespread among prokaryotes, but remain sparsely annotated. We present RASTA-Bacteria, an automated method allowing quick and reliable identification of TA loci in sequenced prokaryotic genomes, whether they are annotated open reading frames or not. The tool successfully confirmed all reported TA systems, and spotted new putative loci upon screening of sequenced genomes. RASTA-Bacteria is publicly available at .